A Surface-Syntactic UD Treebank for Naija - (:unkn) unknown (My University, 2019)
This paper presents a syntactic treebank for spoken Naija, an English pidgincreole, which is rapidly spreading across Nigeria. The syntactic annotation is developed in the Surface-Syntactic Universal Dependency annotation scheme (SUD) (Gerdes et al., 2018) and automatically converted into UD. We present the workflow of the treebank development for this under-resourced language. A crucial step in the syntactic analysis of a spoken language consists in manually adding a markup onto the transcription, indicating the segmentation into major syntactic units and their internal structure. We show that this so-called "macrosyntactic" markup improves parsing results. We also study some iconic syntactic phenomena that clearly distinguish Naija from English.
Keywords: African Research